Low-carbon development of Kuzbass: coal mining and land reclamation - Shutko Larisa (EDP Sciences, 2021)
The purpose of the study is to examine the adaptation of coal mining enterprises to the requirements of the Climate Agenda and the prospects for a low-carbon future of the Kuzbass region. The subject of the research is the impact of coal mining on the conservation of the region’s biocapacity and the future "green" development of Kuzbass on the basis of mine reclamation. The following tasks are tackled: 1. to show the role of mining enterprises in the movement of the region's economy towards a low-carbon future, 2. to determine the relationship between the coal production and the area of mined lands for the period 2013-2019, 3. to reveal the need to increase the mine reclamation rate and conserve the biodiversity of the region's ecosystem, 4. to forecast the growth of the area of mined land with an increase in coal production of more than 300 million tons, provided that the current socio-economic situation in the region remains unchanged. Research methods are elements of a systems approach, regression analysis, building a one-factor linear regression model using the IBM SPSS Statistics software.